Contextualist-retroductive case study design for strategic asset management research. Issue 16 (10th December 2018) - El-Akruti, Khaled; Kiridena, Senevi; Dwight, Richard
Abstract: This paper develops a tailored case study design for strategic asset management research. It draws on the notions of 'contextualist approach' and 'retroductive strategy' used in case study research, and follows the multiple embedded-case design advocated within qualitative research. Using a published asset management research study as a primer, it demonstrates the application of the proposed research design and its methodological rigour. This research design could serve as a reference framework, as well as a research instrument, for guiding asset management research. As such, it facilitates the development of theory that accounts for the multi-faceted nature and current priorities of asset management. Overall, this research design helps determine what activities to be incorporated into an asset management program to enhance an organization's ability to capture value from its operations system. In so doing, it promotes a holistic perspective on asset management that is currently lacking in the literature.